2018
DOI: 10.1001/amajethics.2018.948
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Medical Students’ Negative Bias Toward Patients With Obesity Through Ethics Education

Abstract: Background: Negative bias toward patients with obesity is an ethical challenge in patient care. Several interventions to mitigate medical students' negative weight bias have been tried but none with an explicit focus on ethics. Here we describe first-year medical students' attitudes toward obesity and our effort to improve their attitudes through an innovative ethics session embedded within the required course, "Obesity, Nutrition, and Behavior Change," at Johns Hopkins University School of Medicine.Methods: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“… 85 Existing weight bias reduction interventions aimed at health care students have sought to challenge and reduce beliefs that obesity is within a person's control, evoke empathy, raise awareness, promote weight acceptance and improve communication skills; however, the majority of interventions have only succeeded partially and have been unable to sustain long-term reductions in weight bias. 9 , 48 , 71 , 86 , 87 , 88 Current findings indicate that gender and empathy are significant factors that were associated with weight bias. While weight bias reduction interventions targeting individual genders are impractical, novel, multifaceted interventions to evoke distinct aspects of empathy may produce desirable outcomes, as research has demonstrated the association of low empathic concern with a greater level of generalised prejudice.…”
Section: Discussionmentioning
confidence: 64%
“… 85 Existing weight bias reduction interventions aimed at health care students have sought to challenge and reduce beliefs that obesity is within a person's control, evoke empathy, raise awareness, promote weight acceptance and improve communication skills; however, the majority of interventions have only succeeded partially and have been unable to sustain long-term reductions in weight bias. 9 , 48 , 71 , 86 , 87 , 88 Current findings indicate that gender and empathy are significant factors that were associated with weight bias. While weight bias reduction interventions targeting individual genders are impractical, novel, multifaceted interventions to evoke distinct aspects of empathy may produce desirable outcomes, as research has demonstrated the association of low empathic concern with a greater level of generalised prejudice.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, weight bias persisted after a media-based conditioning intervention, which relied upon the presentation of videos portraying obese people struggling with their weight status and discrimination ( Gapinski et al , 2006 ). An ethics educational training partially improved attitudes towards obesity ( Geller and Watkins, 2018 ), whereas Russell-Mayhew et al (2015) showed a reduction of both implicit and explicit weight bias after performing an interactive professional workshop and O’Brien et al (2010) demonstrated that it was possible to reduce or exacerbate both anti-fat explicit and implicit attitudes, depending on the information provided about causes of obesity. In contrast, Scrivano et al (2017) found that informing about the causes of obesity had an impact only on the explicit beliefs about the controllability of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since weight bias has been found even among medical students ( Miller et al , 2013 ; Phelan et al , 2014 , 2015b ; Baker et al , 2017 ) and within the healthcare setting ( Teachman and brownell, 2001 ; Schwartz et al , 2003 ; Vallis et al , 2007 ; Sabin et al , 2012 ; Tomiyama et al , 2015 ; Aweidah et al , 2016 ; Halvorson et al , 2019 ), the possibility that the quality of patient’s care can be negatively affected, leading people with overweight and obesity to avoid preventive healthcare, should be taken into account. Due to the potential negative implications of weight bias, some researches tried to verify the effects of different manipulations aimed to improve weight stigma ( Geier et al , 2003 ; Teachman et al , 2003 ; Gapinski et al , 2006 ; O’Brien et al , 2010 ; Rukavina et al , 2010 ; Domoff et al , 2012 ; Flint et al , 2013 ; Swift et al , 2013 ; Russell-Mayhew et al , 2015 ; Hilbert and Meyre, 2016 ; Karsay and Schmuck, 2017; Rudolph and Hilbert, 2017 ; Scrivano et al, 2017 ; Geller and Watkins, 2018 ; Wijayatunga et al , 2019 ), providing mixed results, but leading hopes about the possibility that negative attitudes towards fatness can be minimized ( Teachman et al , 2003 ; O’Brien et al , 2010 ; Russell-Mayhew et al , 2015 ; Hilbert and Meyre, 2016 ). A prospective research focusing on medical students ( Phelan et al , 2015b ) found evidence for changes in weight bias, fostered by school training and interactions with patients with obesity, suggesting that curricula and lecturers should be shaped, taking into consideration such mediating variables, in order to improve weight-related attitudes of future professionals.…”
Section: Discussionmentioning
confidence: 99%
“…15 Even if I don't believe these lifestyle choices make a difference in my research, I should still disclose them because of the danger of unconscious bias. 16…”
Section: Discussionmentioning
confidence: 99%